Prove with Example that:-(-) + (-) = ( + )I like a good answer.
-2 (-3) + (-2) = 6 + (-2) = 6 - 2 =4 (where as 4 is a positive)RS for President!
It's not true for all numbers though, like:-1(-1) + (-2) = 1 +(-2) = 1-2 = -1unless you add one more set of brackets:- ( (-) + (-) ) = (+)
You can think of the first negative sign as taking the opposite of what is in the first set of parenthesis. So the opposite of negative 6 is positive 6. And then positive 6 plus negative 5 = positive 1.-(-6) + (-5)6 + (-5)1
if you use "x" with numbers you can get positive result.-(-1x)+(-2x)=3x1x-2x=3x1x=3x+2x1x=5x=5
Let:- represent one seed;+ represent two seeds; and let( and ) both represent a mouth that will eat one seed if there is anything on offer.On the left-hand side we get: 1 seed, eaten. Another seed, eaten. Two seeds, one eaten, one left. Another added but then that one is eaten. Remainder = one seedOn the right-hand side the action is much quicker:A wasted bite (cheating here?!). Two seeds, one eaten. Remainder = one seed
Copyright © 2018 HubPages Inc. and respective owners.
Other product and company names shown may be trademarks of their respective owners.
HubPages® is a registered Service Mark of HubPages, Inc.
HubPages and Hubbers (authors) may earn revenue on this page based on affiliate relationships and advertisements with partners including Amazon, Google, and others.